A perspective on hydrogen energy research, development and innovation activities in Turkey - Arat, Hueseyin T.; Baltacioglu, Mustafa K.; Tanc, Bahattin; Surer, Meryem G.; Dincer, Ibrahim (WILEY, 2020)
Hydrogen can be considered as the most promising fuel towards the greenization. Developed and developing countries around the world have formed their research, investments and directives on hydrogen. The leading countries in this field can be cited as members of the European Union and the United States. Laws and regulations have been shared with the public under the aegis of the established policies. Additionally, determined targets for the short, medium and long term and their feedbacks are recorded by the reports of the competent authorities. Although the Republic of Turkey was aware of the importance of the issue, though there is no open source inventory as disclosed. In Turkey, governmental organization, General Directorate of Energy Affairs (YEGM), and foundations, such as the National Hydrogen Association (NHA), have been encouraging and supporting multidisciplinary studies and activities within the country and internationally. In this study, it is aimed to provide numerical analyses from 1970 to the present by considering hydrogen energy. Related information and data were compiled from online resources on scholarly publications, organizations, groups, books and book chapters, master and doctorate theses, patents received and completed projects. It is also aimed to create a unique information source to refer with respect to planning and activities.
Keywords: Energy & Fuels; Nuclear Science & Technology